Species Identification and Genetic Diversity Analysis of Medicinal Plants Aconitum pendulum Busch and Aconitum flavum Hand.-Mazz - Sun, Jing; Sun, Qing; Li, Xin; Li, Wenjing; Li, Yi; Zhou, Yubi; Hu, Yanping (Plants (Basel), 2024)
The classification system for the genus Aconitum is highly complex. It is also the subject of ongoing debate. Aconitum pendulum Busch and Aconitum flavum Hand.-Mazz. are perennial herbs of the genus Aconitum. Dried roots of these two plants are used in traditional Chinese medicine. In this study, morphological observations and ISSR molecular markers were employed to discriminate between A. flavum and A. pendulum, with the objective of gaining insights into the interspecies classification of Aconitum. The pubescence on the inflorescence of A. flavum was found to be appressed, while that on the inflorescence of A. pendulum was spread. UPGMA (unweighted pair-group method with arithmetic average) cluster analysis, PCoA (principal coordinates analysis), and Bayesian structural analysis divided the 199 individuals (99 individuals from DWM population and 100 individuals from QHL population) into two main branches, which is consistent with the observations of the morphology of pubescence on the inflorescence. These analyses indicated that A. flavum and A. pendulum are distinct species. No diagnostic bands were found between the two species. Two primer combinations (UBC808 and UBC853) were ultimately selected for species identification of A. flavum and A. pendulum. This study revealed high levels of genetic diversity in both A. flavum (He = 0.254, I = 0.395, PPB = 95.85%) and A. pendulum (He = 0.291, I = 0.445, PPB = 94.58%). We may say, therefore, that ISSR molecular markers are useful for distinguishing A. flavum and A. pendulum, and they are also suitable for revealing genetic diversity and population structure.